2022
DOI: 10.1101/2022.07.12.499603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of enhanced innate immune suppression by SARS-CoV-2 Omicron subvariants

Abstract: SARS-CoV-2 adaptation to its human host is evidenced by the emergence of new viral lineages with distinct genotypic and phenotypic characteristics, termed variants of concern (VOCs). Particular VOCs have become sequentially dominant globally (Alpha, Delta, Omicron) with each evolving independently from the ancestral Wuhan strain. Omicron is notable for its large number of Spike mutations found to promote immune escape and re-infection. Most recently, Omicron BA.4 and BA.5 subvariants have emerged with increasi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 85 publications
2
23
0
Order By: Relevance
“…Our nAb panel, built during the last three years of the COVID-19 pandemic, were identified from people receiving two or three mRNA vaccine doses, and from SARS-CoV-2 infected people that had been subsequently vaccinated with the BNT162b2 mRNA vaccine 16,17 . In agreement with previous studies performed mainly with whole sera [6][7][8] , we observed that two mRNA vaccine doses were not sufficient to mount a protective antibody response against omicron variants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our nAb panel, built during the last three years of the COVID-19 pandemic, were identified from people receiving two or three mRNA vaccine doses, and from SARS-CoV-2 infected people that had been subsequently vaccinated with the BNT162b2 mRNA vaccine 16,17 . In agreement with previous studies performed mainly with whole sera [6][7][8] , we observed that two mRNA vaccine doses were not sufficient to mount a protective antibody response against omicron variants.…”
Section: Discussionsupporting
confidence: 91%
“…Different scenarios could explain the fast spreading of these new sublineages and the ability to outcompete previous omicron variants. Examples are the lack of the G496S mutation in the Spike (S) protein, which results in increased human angiotensin-converting enzyme 2 (hACE2) binding affinities compared to other omicron variants 5 , the evolution of novel mutations on the S protein, which conferred enhanced resistance to neutralizing antibodies 6 , and the ability to better suppress and antagonize the innate immune defenses 7 . The SARS-CoV-2 neutralizing antibodies target the receptor binding domain (RBD) and N terminal domain (NTD) of the S protein, which is a trimeric glycoprotein exposed on the surface of the virus 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…51 Importantly, the emerging SARS-CoV-2 Omicron subvariants BA.4 and BA.5 are notable for their ability to enhance innate immune suppression. 52 Thus, in addition to demonstrating potent antiviral effects in the COVID-19 mouse model, our results demonstrate that these duplex RNAs can overcome viral antagonism of human innate immunity, at least in human lung epithelial and endothelial cells maintained in organ chips that have been previously shown to recapitulate human lung pathophysiology with high fidelity. 53,54…”
Section: While Much Has Been Learned About the Molecular Features Of ...mentioning
confidence: 52%
“…Based on these data and our previous observations (52), we next hypothesized that Omicron subvariants evolved enhanced innate immune suppression by modulating the expression of specific viral proteins known to inhibit interferon responses. Interrogation of global viral RNA and protein expression during infection revealed differences in the production of structural and accessory proteins, but not non-structural proteins, across the Omicron subvariants (Fig.…”
Section: Omicron Subvariants Evolved Innate Immune Antagonism By Modu...mentioning
confidence: 69%